Web-Based Thermochemistry Media: Potential for ESD-Oriented Implementation - Aries Setyo Wibowo; Siti Patonah; Mega Novita (Jurusan Pendidikan Kimia Universitas Halu Oleo, 2025)
The purpose of the research is to identify the potential for using educational media, such as websites that focus on Education for Sustainable Development (ESD), in thermochemistry materials. Data was gathered using a descriptive qualitative approach through observation, surveys, interviews, and an analysis of the teaching materials from 10 chemistry teachers and 72 11th-grade students at SMAN 1 Kedungwuni. The results show that 80% of teachers fall into the Proficient category, and all respondents (100%) expressed some or a great deal of agreement with the use of website-based media. About 40% of teachers have already integrated ESD, 40% understand it but have not yet implemented it, and 20% do not understand it. According to the analysis module, just 38% of the material fully explains ESD. According to 89% of respondents, media websites are effective in visualizing abstract concepts and have a high potential for implementation